ENHANCING DAYLIGHT IN DEEP-PLAN OFFICES FOR NIGERIA'S TROPICAL CLIMATE: A LIGHT PIPE APPROACH - Mukhtar, Faruk Ibrahim; Salisu, Abubakar Sadiq; Salihu, Murtala Muhammad (Journal of Architecture, Planning and Construction Management, 2024)
This research addresses the challenge of maximising daylight provision in deep-plan office buildings in Nigeria's tropical wet and dry climate. It investigates the effectiveness of horizontal light pipes at 5m, 10m, and 15m, employing a mixed-method approach that combines case studies and computer simulations. The study utilises Climate Studio for Rhinoceros 3D as the simulation tool to assess light distribution uniformity and illuminance levels in deep-plan offices. Statistical analysis includes applying ANOVA tests to ascertain the significance of differences between various light pipe configurations. Findings reveal that the 10m light pipe configuration consistently outperforms the 5m and 15m options, providing superior uniformity of light distribution and higher illuminance levels, thereby maximising daylight provision. The study recommends the 10m light pipe configuration as optimal for maximising daylight provision in deep-plan office buildings within Nigeria's tropical wet and dry climate.